Quality Control pada PT. Yakult Indonesia Persada - M. Rixza; Siti Maftukhah; Eka Ardiansyah; Toba Fathir Auladya; Joko Purwanto (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
This article examines the implementation of the Quality Control (QC) system at PT Yakult Indonesia Persada as part of the Field Work Lecture (KKL) activities. The main focus of the research is how the company maintains the consistency of the quality of probiotic products through thorough quality control. This research aims to provide an in-depth understanding of the implementation of QC which includes physical, chemical, microbiological testing, and quality assurance of production equipment. The methods used are direct observation in the field and literature review related to food quality standards. The results of the observation show that PT Yakult applies the principles of Good Manufacturing Practices (GMP), Statistical Process Control (SPC), and Total Quality Management (TQM) in an integrated manner in the entire production process. Quality control is carried out through Specific Gravity (SG), pH, and the number of Lactobacillus casei Shirota bacteria with a minimum standard of 6.5 billion per bottle. In addition, sterilization of production equipment is carried out in layers and validated through laboratory tests, and is supported by systematic recording of test results. These findings show that the QC system at PT Yakult not only focuses on the final product, but also covers the entire production stage. With this approach, the company is able to consistently ensure the quality, safety, and health benefits of products, as well as meet applicable food industry standards.